2017
DOI: 10.1515/bjes-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation Formats of China and Europe: Synergies and Divergences

Abstract: This contribution articulates the synergies and divergences of the various formats of cooperation between China and the European countries. The EU and China have a strong interest in each other’s flagship initiatives, namely the Investment Plan for Europe, and the One Belt, One Road Initiative (Silk Road Economic Belt and 21st-Century Maritime Silk Road). The authors argue that there are certain synergies between these initiatives. Furthermore, the new initiative EU-China Connectivity Platform is aimed to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…Given that CEEC countries are relatively small compared to China, it was pointed out that a regional approach involving China on the one hand and the 17 CEEC on the other is the right way to institutionalize cooperation [1][2][3]. A series of studies highlighted the need for the 17 CEEC to diversify in terms of foreign trade and investment, which encouraged them to strive for closer economic relations with China [4][5][6]. A study by Stanojevic, Qiu and Chen (2020) [7] examined export competition between the EU15 (so-called old EU members) and China in the 16 CEEC markets (Greece was not a part of the cooperation mechanism at the time).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given that CEEC countries are relatively small compared to China, it was pointed out that a regional approach involving China on the one hand and the 17 CEEC on the other is the right way to institutionalize cooperation [1][2][3]. A series of studies highlighted the need for the 17 CEEC to diversify in terms of foreign trade and investment, which encouraged them to strive for closer economic relations with China [4][5][6]. A study by Stanojevic, Qiu and Chen (2020) [7] examined export competition between the EU15 (so-called old EU members) and China in the 16 CEEC markets (Greece was not a part of the cooperation mechanism at the time).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On one hand, some scholars tend to be more optimistic, believing the resultant economic development and connectivity will help stabilize China's border regions, secure its energy supplies and allow it to extend its strategic influence (Wuthnow, 2017). Šteinbuka articulated the synergies and divergences of the various formats of cooperation between China and European countries (Šteinbuka et al , 2017). Wilson (2016) analyzed that both Russia and China have launched ambitious regional projects, promoted as means of strengthening linkages with neighboring states; the author also located this development in the context of Russia's and China's extended foreign policy goals, and its implications for Russian–Chinese relations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rising collaboration of the Chinese and CEE nations including CR has spawned far-reaching criticism by other western nations who thinks that it not a healthy relation. However, Šteinbuka, Muravska and Kuznieks [7] concluded that China-CEE cooperation does not contradict the EU investment plan, and that none of the two parties is aiming to abate the union. They believed that the EU to which CR belong and China have a great interest in each other's top development plans.…”
Section: Review Of Related Literaturementioning
confidence: 99%